Juventudes, subjetivação e violências: inventando modos de existência no contemporâneo - Takeiti, Beatriz Akemi (2014)
This study is based on a denaturalizing perspective of youth violence, through narratives on young people existence ways, especially those who are forged by the invention of cultural practices on the peripheries. This study aims to identify and analyze, in the light of Michel Foucault s contributions, youth subjectivity ways in contexts of increasing vulnerability. We focused on the analysis of the effects of violence in the production of subjectivities, as well as the strategies by which the young people reverse the periphery stigma. For both, we followed three subjects engaged in different cultural collective activities - marginal literature presentations, hip-hop movement and audiovisual production - during the year 2012 in the districts of Brasilândia and Vila Nova Cachoeirinha in the northern zone of São Paulo state. We conducted interviews in both oral history and ethnographic experiments in the territory in which they resided. When making a written defense, committed to a policy of narrative, we decided to start this thesis from Jorge s story, our main interlocutor and thread. These stories are not only on migrations, land occupations, poverty, violence, but also on creative collective productions, new ways of living woven through aesthetic inventions in the periphery. We point out two different moments, but interconnected which showed the effects of violence in the youth subjectivity ways. The first moment, presented in the Part II, shows as the periphery has emerged as a live-territory and contributed to the construction of existential territories of young people. This territorying is what operates a certain youthful positioning as if the young man, black man and poor man stigma from this place to the emblem, to the pride of being from the periphery. This way, at the second moment, in the Part III, we highlight how these cultural collective activities, such as the Poesia da Brasa poetry presentation and the Cinescadão , invoke a form of resistance, turning the experiences of violence and vulnerable moments lived in the peripheries into ethical, aesthetic and political practices. This way, the adoption of the narratives as a method does not only express a methodological concern about the procedures we used with the subject matter, but also demarcates, primarily, a political stance, an ethos of the researcher in the development of the study: the one which does not separate the production of knowledge / from the writing production subjectivity policy